Opportunities and Challenges in Cooperative Road Vehicle Automation - Steven E. Shladover (IEEE Open Journal of Intelligent Transportation Systems, 2021)
This paper provides an introduction to the opportunities for improving the performance of road transportation automation systems by use of vehicle-vehicle and vehicle-infrastructure communication and cooperation. Four different types of cooperative driving automation are defined and examples of the functionality enabled by each are described. Although the benefits of cooperative automation are significant, there are also significant challenges to its widespread deployment, which are also described. The risks of over-reliance on communication for cooperative automation implementations are also discussed to provide a balanced view of appropriate levels of cooperation.